Photosynthesis and enzyme activities regulating starch biosynthesis in different varieties of sweet potato (Ipomoea batatas Lam.) - Aswini Krishnan N K (Department of Plant Biotechnology, College of Agriculture, 2016)
The present study entitled “Photosynthesis and Enzyme activities regulating starch biosynthesis in different varieties of Sweet potato (Ipomoeabatatas Lam.)” was conducted at ICAR-CTCRI, Trivandrum during the period 2015-2016. The objective of the work was to the study the relation between photosynthesis, leaf area and enzyme activities involved in regulating starch biosynthesis in different genotypes of sweet potato and to identify the limiting factor(s) in low starch varieties of Sweet potato. The rate of photosynthesis, morphological and biochemical parameters and enzymes activities involved in the starch biosynthesis were recorded at monthly intervals in selected varieties. Morphological parameters such as total number of leaves per plant, leaf area and tuber yield per plant were recorded during 1 to 4 MAP. Rate of photosynthesis was measured using IRGA (infra-red gas analyzer). The leaf area and photosynthetic rate were directly increasing the productivity which was found to be higher in the Sree Arun and Kanhangad variety. Biochemical parameters such as sucrose and starch content were estimated in leaves and tubers of sweet potato varieties. The sucrose content was relatively higher in leaves of Kanhangad variety and in tubers of ST-13 variety. Starch content was higher in the variety Sree Arun which had a direct relation with the photosynthetic rate and tuber yield. Activities of enzymes such as AGPase, starch synthase (SS), sucrose phosphate synthase (SPS), sucrose synthase (SuSy) and invertase were measured in both the leaves and tubers of sweet potato. AGPase and SS were directly involved in the tuberization throughout the development which was observed in Sree Arun variety. SPS was highly active in leaves than tubers. SuSy and invertase are mainly involved in the sucrose metabolism in leaves and highly active during the day time. The increased activity of AGPase and SS in sweet potato tubers will open a new strategy for bioengineering the efficiency of enzymes to improve the starch content in low yielding sweet potato varieties. A detailed molecular study on enzymes involved in starch biosynthesis will be necessary for increasing or improving the starch content in tuber crops.